2014
DOI: 10.1103/physrevc.89.025803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermionic dark matter on properties of neutron stars

Abstract: By assuming that only gravitation exists between dark matter (DM) and normal matter (NM), we study the effects of fermionic DM on the properties of neutron stars using the two-fluid Tolman-Oppenheimer-Volkoff formalism. It is found that the mass-radius relationship of the DM admixed neutron stars (DANSs) depends sensitively on the mass of DM candidates, the amount of DM, and interactions among DM candidates. The existence of DM in DANSs results in a spread of mass-radius relationships that cannot be interprete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 61 publications
2
61
0
Order By: Relevance
“…Since dark matter interacts with normal baryonic matter through gravity, it is quite possible for white dwarfs and neutron stars to accrete dark matter and evolve to a dark matter admixed compact star [12,15,17,[21][22][23][24][25][26]. The large baryonic density in compact stars increases the probability of dark matter capture within the star and eventually results in gravitational trapping.…”
Section: Introductionmentioning
confidence: 99%
“…Since dark matter interacts with normal baryonic matter through gravity, it is quite possible for white dwarfs and neutron stars to accrete dark matter and evolve to a dark matter admixed compact star [12,15,17,[21][22][23][24][25][26]. The large baryonic density in compact stars increases the probability of dark matter capture within the star and eventually results in gravitational trapping.…”
Section: Introductionmentioning
confidence: 99%
“…We are now able to derive an expression of the QFI thanks to results from [28] and expressions for fidelity between Gaussian states [32]. One can also use the derivations in [33][34][35] which are applications of the results in [28] to Gaussian states. As expected, all these expressions of the QFI for Gaussian states are functions of the first and second moment of the quadrature operators.…”
Section: Derivation Of the Metrological Quantities For Gaussian mentioning
confidence: 99%
“…Efforts have been made to find alternatives [28][29][30][31], but they are still hard to apply for arbitrary dynamics and states. We restrict ourselves to Gaussian states which are more easily accessible experimentally and for which [33][34][35] have derived explicit expressions of the QFI. As we will see in the following, this important assumption also guarantees that the best measurement is a quadrature measurement and that the maximum likelihood estimator is efficient implying that the quantum Cramer-Rao bound Eq.…”
Section: Derivation Of the Metrological Quantities For Gaussian mentioning
confidence: 99%
“…The results clearly show that large values ofhω (corresponding to thin barriers and then in favour to a fusion enhancement) are always associated with positive Q values for neutron transfer, in both medium (Ca+Ca, Si+Ni, Ni+Ni) and heavy systems (Ca+Zr, Ca+Sn, Ni+Sn). In particular, excitation functions have a shallower slope for systems where a neutron-poor projectile collides on a neutron-rich target [14].…”
mentioning
confidence: 99%
“…Two recent publications, concerning the influence of transfer in the fusion process, came to different conclusions. In the first one [13], where the excitation function of 58 Ni+ 132 Sn could only be measured down to the 0.1-1 mb region due to the low intensity of the secondary 132 Sn beam, it was claimed that the influence of transfer for Ni+Sn is negligible compared to lighter systems; in the other one [14] it was concluded that the fusion enhancement due to transfer couplings should be present in heavier systems as well.…”
mentioning
confidence: 99%